Correlation between coal structure and release of the two organic compounds during pyrolysis. (1st April 2015) - Yan, Lunjing; Bai, Yonghui; Zhao, Ruifang; Li, Fan; Xie, Kechang
Highlights: The release principle of organic compounds is associated to coal structure during pyrolysis. The release amounts of PAHs and phenols has different trend as coal rank increased. The formation mechanisms of PAHs and phenols are proposed during coal pyrolysis. Abstracts: A considerable amount of organic compounds could be released during coal utilization processes, and these compounds could have a significant detrimental effect on the environment and human health if freely discharged. In this study, we investigated the yields of two organic compounds (PAHs and phenols) released during the pyrolysis of coals with different ranks. And then, the formation mechanisms of PAHs and phenols are discussed by means of comparisons the correlation between release principles and coal structure. The results showed that the yields of PAHs and phenols depended to a large extent on coal structure. PAHs are formed not only by thermal breakdown of coal structure, but also by the combination of different low molecule weight compounds with each other. Monohydric phenolic carbon and aromatic ether carbon were likely to be the precursor structure of phenols. The formation of phenol, cresol and xylenol are closely related to the types of free radical (like H or CH3 ) and the chemical structure of oxygenated aromatic carbon in coal during pyrolysis.